Analysis of the Use of Financial Technology and Financial Literacy Among MSMEs - Novia Utami (MBIA, 2023)
The massive effects of the Covid-19 pandemic and continuous technological innovations are not the only ones that change people's lives; the world is now experiencing the emergence of FinTech. FinTech is a technology-based financial service that allows financial transactions to be made quickly, anywhere, and anytime. FinTech has given MSMEs advantages, from capital financing to easy transaction processes to boost MSMEs' growth. This research aims to see how the adoption of FinTech and financial literacy affect the development of Indonesia's MSMEs. Data were used online questionnaires while samples were selected using a convenience sampling technique with 125 business owners participating in this research. Data were then analyzed using the OLS regression method. Results suggest that FinTech and financial literacy positively and significantly influence the development of MSMEs. Keywords: Financial Technology, Financial Literacy, MSME Abstrak Efek terjadinya pandemi Covid19 dan inovasi teknologi yang tidak terbatas pada era digital saat ini, semakin dilengkapi dengan hadirnya FinTech. FinTech adalah layanan keuangan dengan berbasis teknologi yang memberikan kemudahan dalam bertransaksi keuangan dimanapun dan kapanpun. FinTech menjadi keunggulan tersendiri bagi UMKM, baik dari segi pembiayaan permodalan maupun kemudahan bertransaksi untuk meningkatkan perkembangan UMKM. Penelitian ini bertujuan untuk mengetahui pemanfaatan Fintech dan literasi keuangan terhadap perkembangan UMKM di Indonesia. Data dalam penelitian ini diperoleh melalui kuesioner secara online dan pengambilan sampel menggunakan teknik convenience sampling. Dengan menggunakan 125 responden pemilik usaha dan metode regresi OLS, penulis menemukan bahwa Fintech dan literasi keuangan memiliki pengaruh positif signifikan terhadap perkembangan UMKM. Kata kunci: Financial Technology, Literasi Keuangan, UMKM